Recollecting Wondrous Moments: Father Pushkin, Mother Russia, and Intertextual Memory in Tatyana Tolstaya's "Night" and "Limpopo" - Karen R. Smith (Studies in 20th & 21st Century Literature, 2004)
With their references to Alexander Pushkin, Tolstaya's "Night" and "Limpopo" respond to the cultural crisis of 1980s Russia, where literary language, bent for so long into the service of totalitarianism, suffers the scars of amnesia. Recycling Pushkin's tropes, particularly his images of feminine inspiration derived from the cultural archetype of Mother Russia, Tolstaya's stories appear nostalgically to rescue Russia's literary memory, but they also accentuate the crisis of the present, the gap between the apparel of literary language and that which it purports to clothe. "Night," an ironic reworking of Pushkin's "Queen of Spades," dismantles the nostalgic imagery of his "Winter Evening." In "Limpopo" the resurrection of Pushkin's feminine muse from his 1825 "To ..." challenges the linear temporality that shapes claims for eternal influence made in "I will build a memorial to myself...." In both stories, Tolstaya exploits paradoxes within Pushkin's œuvre to explore oppositions—present vs. past, cultural expression vs. experience—that limit literary representation in her own time. Tolstaya's allusions to Pushkin ultimately express cynicism about the capacity of literary language to provide authenticity in the wake of totalitarianism, but they also celebrate its persistence as an alternative life force that tears through the deadening banality of Soviet routine.
Keywords: Alexander Pushkin; Tolstaya; Night; Limpopo; 1980s Russia; cultural crisis; Russia; literary language; totalitarianism; feminine inspiration; Mother Russia; nostalgia; Russia' s literary memory; memory; clothe; irony; Queen of Spades; Winter Evening; feminine muse; To ...; paradoxes; œuvre; present vs. past; present; past; cultural expression; experience; representation; authenticity; Soviet; Soviet Russia